The Poetry of Cao Zhi - Cutter, Robert Joe (Library of Chinese Humanities, 2021)
This is the first complete translation of the poetry of Cao Zhi, a major figure from the formative age of classical Chinese poetry. The translations take the reader beyond anthology pieces to present a more complete view of the literary practices and concerns of Cao Zhi and his contemporaries. A number of works not previously available in English are included here, enhancing our understanding of the culture of China's early medieval period.